Gas turbine shaft over-speed / failure modelling: aero/thermodynamics modelling and overall engine system response - Soria, Carlos (Cranfield University, 2014)
Gas turbine design needs of high-speed turbomachinery whose layout is organised in compressor-turbine pairs mechanically linked by concentric shafts. The mechanical failure of a shaft leads to compressor-turbine decoupling provoking the acceleration of the free-running turbine. In view of such scenario, it is of paramount importance to guaranty the mechanical integrity of the turbine, in terms of high energy debris release. Certification authorities require proof that any possible failure will be contained; admitting the reliable simulation capability of the event as certification strategy. The objectives of this research activity have aimed at the development of reliable simulation tools based on analytical and semi-empirical models. The integration of all the different models/modules together in an “all-in-one” tool provides the sponsor company with the capability to simulate and assess various shaft over-speed scenarios during the early stages of an engine's design and development program. Shaft failure event cannot be understood unless engine components interaction and fast transient effects are taken into account in a global manner. The high vibration level consequence of the breakage, or the thermodynamic mismatch due to the rapid free-running compressor deceleration, trigger the surge of the compression system which affects to the performance of every engine component. Fully-transient simulation capability to model compression system post-stall performance and secondary air system behaviour has been developed. Component map prediction tools have been created for compressor reverse flow performance and turbines affected by inlet distorted flows. The development of the so-called “all-in-one” simulation tool has been completed and it has been applied to the modelling of a real case of shaft failure. Reliable prediction of thermodynamic properties evolution and over-speeding turbine terminal speed have been shown. The robustness and flexibility of the simulation tool have been demonstrated by its application to different theoretical scenarios.